2013
DOI: 10.2753/pin1099-9922150201
|View full text |Cite
|
Sign up to set email alerts
|

Can Integrity Be Taught in Public Organizations?

Abstract: Integrity-training programs for civil servants are assumed to be useful, but there is little or no empirical proof for this claim. The effectiveness of two Dutch training programs was examined through a study conducted with several hundred municipal officials. One of the two programs was found to be effective only in the short term, and neither appears to be effective in the long term. The article concludes with some recommendations for further research. keywords: experimental research design, integrity-traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…This would target specific rationalizations to which public officials would be more susceptible, such as the denial of individual responsibility, rather than rationalizations to which they would not, such as the metaphor of the ledger. Anti-corruption efforts implemented in business settings have been applied to the public sector, but the results have been mixed at best (Craft, 2010;Rosenson, 2009;van Montfort, Beck, & Twijnstra, 2013). One study found that mandated ethics programs are ineffective when the values they embody do not match the local moral culture (Fording, Miller, & Patton, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…This would target specific rationalizations to which public officials would be more susceptible, such as the denial of individual responsibility, rather than rationalizations to which they would not, such as the metaphor of the ledger. Anti-corruption efforts implemented in business settings have been applied to the public sector, but the results have been mixed at best (Craft, 2010;Rosenson, 2009;van Montfort, Beck, & Twijnstra, 2013). One study found that mandated ethics programs are ineffective when the values they embody do not match the local moral culture (Fording, Miller, & Patton, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Collaborative approaches among agencies and jurisdictions and the public reporting of experiences with, and outcomes of, new methods can greatly enrich knowledge within the field. Further, as Van Montfort and colleagues (2013: 118) highlight, more studies that seek to empirically identify the specific factors that contribute to positive or negative outcomes in educational approaches, among particular participants, or in different learning contexts, are needed to inform both the design of evaluations and the implementation of integrity education itself.…”
Section: Resultsmentioning
confidence: 99%
“…Integrity in public administration is increasingly in the spotlight. Broadly, behaving with integrity encompasses three aspects—moral awareness, reasoning, and behavior (Van Montfort et al, 2013: 118)—but the application of standards remains contentious, while precisely measuring the dimensions of problems involving contrary behavior is difficult (see, for example, Cochrane, 2018; Sampford et al, 2006). Nevertheless, with evidence of declining public trust in government institutions (see, for example, Appleby et al, 2016; Hetherington and Rudolph, 2008), the demands on the public sector to meet the highest possible integrity standards have never been greater.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations